Bridging biodiversity and regenerative development : Conceptual groundwork for life-affirming relationships - Veijalainen, Anu; Salo, Matti; Rouhiainen, Henna; Räikkönen, Juulia; Sääksjärvi, Ilari E. (Springer Nature, 2026)
The global decline of biodiversity demands transformative change that realigns human activity with planetary processes. Regenerative development may facilitate systemic transformation but remains underexamined in relation to biodiversity. We explore the relationship between biodiversity and place regeneration, conceptually aligning biodiversity enhancement and regenerative development. This requires adopting a refocused concept of biodiversity as a dynamic, relational attribute of life that engenders biocultural diversity. Similarly, regenerative development promotes co-evolving, life-affirming relationships within and between human and natural systems. Regenerative design may catalyse regenerative development capacity in communities by engaging participants in regenerative dynamics, potentially increasing biodiversity. However, the intentional incorporation of actions explicitly aimed at enhancing biodiversity remains necessary. Challenges persist due to entrenched anthropocentric worldviews and the difficulty of including human expressions within biodiversity. The refocused biodiversity concept offers a feasible leverage point for fostering transformative change within the narrowing timeframes to halt biodiversity decline.
Keywords: diversity; planetary boundaries; regeneration; social-ecological systems; sustainability; worldviews